2016
DOI: 10.1371/journal.pone.0168650
|View full text |Cite
|
Sign up to set email alerts
|

Knocking Down the Expression of GMPase Gene OsVTC1-1 Decreases Salt Tolerance of Rice at Seedling and Reproductive Stages

Abstract: Salinity is a severe environmental stress that greatly impairs production of crops worldwide. Previous studies have shown that GMPase plays an important role in tolerance of plants to salt stress at vegetative stage. However, the function of GMPase in plant responses to salt stress at reproductive stage remains unclear. Studies have shown that heterologous expression of rice GMPase OsVTC1-1 enhanced salt tolerance of tobacco seedlings, but the native role of OsVTC1-1 in salt stress tolerance of rice is unknown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 65 publications
0
23
0
Order By: Relevance
“…Inhibiting the expression of OsVTC1-3 resulted in the rapid accumulation of H 2 O 2 in rice roots under salt stress; in contrast, there was no obvious H 2 O 2 accumulation in rice leaves ( Figure 3 ). Different from OsVTC1-3 , the previous study showed that rice GMPase gene OsVTC1-1 played an important role in scavenging ROS in rice leaves [ 28 ], indicating that rice GMPase homologous genes OsVTC1-1 and OsVTC1-3 may be involved in the salt response in rice different organs, OsVTC1-1 in leaves and OsVTC1-3 in roots by regulating ROS dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inhibiting the expression of OsVTC1-3 resulted in the rapid accumulation of H 2 O 2 in rice roots under salt stress; in contrast, there was no obvious H 2 O 2 accumulation in rice leaves ( Figure 3 ). Different from OsVTC1-3 , the previous study showed that rice GMPase gene OsVTC1-1 played an important role in scavenging ROS in rice leaves [ 28 ], indicating that rice GMPase homologous genes OsVTC1-1 and OsVTC1-3 may be involved in the salt response in rice different organs, OsVTC1-1 in leaves and OsVTC1-3 in roots by regulating ROS dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…The exogenous AsA rescued most tolerance of OsVTC1-3 RI plants to salt stress, showing that the role of OsVTC1-3 in regulating AsA synthesis was important for rice roots to scavenge ROS and enhance the tolerance of rice to salt stress ( Figure 4 ) Salt stress rapidly induced OsVTC1-3 expression and increased AsA biosynthesis in rice roots ( Figure 1 ), and decreasing the expression of OsVTC1-3 significantly impaired the salt-induced AsA synthesis in rice roots ( Figure 5 ), indicating that OsVTC1-3 is involved in rice salt response by regulating AsA synthesis in rice roots under salt stress. In contrast, the homologous OsVTC1-1 played an important role in salt response in rice leaves due to regulating AsA biosynthesis in rice leaves [ 17 , 28 ]. In all, the results from the present work suggested that, different from homologous OsVTC1-1 , which regulates AsA biosynthesis and the salt response of rice leaves, rice can specifically activate the transcript of OsVTC1-3 in rice roots to promote AsA synthesis to scavenge ROS in rice roots to improve the salt tolerance of rice under salt stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Arabidopsis, Atvtc1-1 (GMP) mutant shows impaired production of AsA (Conklin et al ), and an enhancement of salt tolerance was associated to the binding of AtERF98 to the AtVTC1–1 promoter. Moreover, knocking down the expression of rice GMP gene decreases its salt tolerance (Qin et al ). The next step in this pathway, the conversion of GDP‐ d ‐mannose to GDP‐ l ‐Galactose (GDP‐ l ‐Gal), is catalyzed by GDP‐ d ‐mannose–30, 50‐epimerase (GME).…”
Section: Resultsmentioning
confidence: 99%
“…The overexpression of APX genes in rice reduces ROS levels and enhances salt tolerance [73][74][75]. The knockdown of OsVTC1-1 and OsVTC1-3, which are involved in ascorbate synthesis, increases the accumulation of ROS and decreases the salt resistance of rice [76][77][78].…”
Section: Mapping and Cloning Of Salt-tolerant Genes/qtlsmentioning
confidence: 99%